IMPROVING THE TREATMENT OF CORONAVIRUS INFECTION COVID-19 - Pulat M. Abilov; Bakhtiyor U. Iriskulov; Ozoda Z. Saydalikhodjaeva; Zukhra N. Boboeva; Sevara B. Azimova; Gulchekhra E. Usmonova (Central Asian Journal of Medicine, 2023)
This article provides data on a new method of treating coronavirus infection COVID-19 with a mixture of Ganoderma Lucidum and Alhadai. When performing PCR diagnostics, 110 copies / ml were found in the blood of rats on days 5-6, which indicates high levels of the virus in the respiratory tract. The viral RNA detection rate was 95%. Ganoderma Lucidum contains a large number of amino acids, both essential and non-essential, which bind to the protease domain of ACE 2 or to the S-protein of SARS CoV-2 and prevent the two substances from binding. Thus, there is no excessive accumulation of angiotensin II, which, through the activation of AT1R (angiotensin II receptor type I), leads to acute lung injury.